2002
DOI: 10.1118/1.1513568
|View full text |Cite
|
Sign up to set email alerts
|

Analytical representation of enhanced dynamic wedge factors for symmetric and asymmetric photon fields

Abstract: The Enhanced Dynamic Wedge (EDW) presents many advantages over the physical wedge. However, in order to calculate monitor units (MUs) necessary to deliver a certain dose at a certain point, EDW factors (EDWFs) need to be determined. In this work, based on analysis of the golden segmented treatment table (GSTT) and the MU fraction model, an empirical analytic formula has been developed to calculate EDW factors for symmetric and asymmetric fields. This formalism is an extension of the MU fraction model. However … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…It should also be mentioned that Gibbons 10 earlier developed a more complicated analytical model for EDW factors. Although according to earlier studies, 10,11 compared to FMA their models appear to reduce the discrepancies between the measured and calculated wedge factors at the center of field, our study 12 found that FMA actually performs no worse than the models by Gibbons and Yu. While satisfactory agreement between calculated and measured center-of-field EDW factors has been reported, the above-mentioned analytical models generally fail to accurately predict wedge factors at off-center points ͑see Sec. III͒.…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…It should also be mentioned that Gibbons 10 earlier developed a more complicated analytical model for EDW factors. Although according to earlier studies, 10,11 compared to FMA their models appear to reduce the discrepancies between the measured and calculated wedge factors at the center of field, our study 12 found that FMA actually performs no worse than the models by Gibbons and Yu. While satisfactory agreement between calculated and measured center-of-field EDW factors has been reported, the above-mentioned analytical models generally fail to accurately predict wedge factors at off-center points ͑see Sec. III͒.…”
Section: Introductioncontrasting
confidence: 49%
“…͑8͒. Letters "B" and "C" in the same figures describe the agreement between the measured wedge factors and factors calculated with the help of the FMA and the model by Yu,11 respectively. Comparison between measured and calculated WFs at off-center points for different symmetric and asymmetric fields, wedge angles, and photon energies are shown in Tables II and III. More specifically, the latter tables contain maximum and average absolute diff͑%͒ obtained by using Eq.…”
Section: Iiic2 Off-center Wedge Factorsmentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, Yu 98 and Kuperman 99 modified the MU fraction model by shifting the calculation point in the Y-direction (i.e., along the direction of jaw motion), although the magnitude and field size dependence of this shift is controversial. 100 The methods above also apply for calculations to points along the principal axis in the wedge-gradient direction.…”
Section: B1ii Physical Wedges a Number Of Investigatorsmentioning
confidence: 99%
“…By its dynamic nature it inherently presents more difficulty in accurate output predictions than the static PW. This is clearly evident in the amount of published material that has appeared in the literature over recent years 10,[14][15][16][19][20][21][22][23][24] . The EDW factor, unlike the PW factor, varies significantly with field size and must be accurately predicted for the field size employed if an accurate determination of MU is to be achieved.…”
Section: Enhanced Dynamic Wedge Implementationmentioning
confidence: 95%